Disease Severity in Moderate-to-Severe COVID-19 Is Associated With Platelet Hyperreactivity and Innate Immune Activation - Jakobs, Kai; Reinshagen, Leander; Puccini, Marianna; Friebel, Julian; Wilde, Anne-Christin Beatrice; Alsheik, Ayman; Rroku, Andi; Landmesser, Ulf; Haghikia, Arash; Kränkel, Nicolle; Rauch-Kröhnert, Ursula (Frontiers in Immunology, 2022)
Background Hemostasis and inflammation are both dysregulated in patients with moderate-to-severe coronavirus disease 2019 (COVID-19). Yet, both processes can also be disturbed in patients with other respiratory diseases, and the interactions between coagulation, inflammation, and disease severity specific to COVID-19 are still vague. Methods Hospitalized patients with acute respiratory symptoms and with severe acute respiratory syndrome coronavirus 2 (SARS-CoV2)-positive (COVpos) and SARS-CoV2-negative (COVneg) status were included. We assessed adenosine diphosphate (ADP)-, thrombin receptor activator peptide 6 (TRAP)-, and arachidonic acid (AA)-induced platelet reactivity by impedance aggregometry, as well as leukocyte subtype spectrum and platelet-leukocyte aggregates by flow cytometry and inflammatory cytokines by cytometric bead array. Results ADP-, TRAP-, and AA-induced platelet reactivity was significantly higher in COVpos than in COVneg patients. Disease severity, assessed by sequential organ failure assessment (SOFA) score, was higher in COVpos than in COVneg patients and again higher in deceased COVpos patients than in surviving COVpos. The SOFA score correlated significantly with the mean platelet volume and TRAP-induced platelet aggregability. A larger percentage of classical and intermediate monocytes, and of CD4pos T cells (TH) aggregated with platelets in COVpos than in COVneg patients. Interleukin (IL)-1 receptor antagonist (RA) and IL-6 levels were higher in COVpos than in COVneg patients and again higher in deceased COVpos patients than in surviving COVpos. IL-1RA and IL-6 levels correlated with the SOFA score in COVpos but not in COVneg patients. In both respiratory disease groups, absolute levels of B-cell-platelet aggregates and NK-cell-platelet aggregates were correlated with ex vivo platelet aggegation upon stimulation with AA and ADP, respectively, indicating a universal, but not a COVID-19-specific mechanism. Conclusion In moderate-to-severe COVID-19, but not in other respiratory diseases, disease severity was associated with platelet hyperreactivity and a typical inflammatory signature. In addition to a severe inflammatory response, platelet hyperreactivity associated to a worse clinical outcome in patients with COVID-19, pointing to the importance of antithrombotic therapy for reducing disease severity.